Ποιοτική και ποσοτική ανάλυση και σύγκριση επιφανειών μεταλλικών εμφυτευμάτων πριν και μετά την εμφύτευση - Λαγού, Ηλιάδα (Τμήμα Μηχανολόγων Μηχανικών και Επιστήμης και Μηχανικής Υλικών, Σχολή Μηχανικής και Τεχνολογίας, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2012)
Implanting stents is nowadays a common method so that the blood flow in tight arteries is restored.Despite the development of medical methods, there are still important disadvantages in the use of those implants.The corrosion of the stents, as well as their unsuccessfulness, while inside the human body, constitutes an important factor for the appearance of in-stents restenosis.Therefore, it was considered important to investigate the damage that could be caused in stents, according to their building material, while being implanted in tubes with different geometry - something which was dealt with in this research.The following has been investigated: the dynamic charge in three geometries, in a straight tube, in a small-bent tube, and in a large-bent tube.The samples were placed in mock arteries, that is in latex tubes, that resembles the human artery, and were subjected to a specific number of cycles with the help of the Bose Electron 9110 Stent / Graft test machine as a resemblance of human blood.During the completion of the test, the samples were removed and cleaned, in order to be analysed for damages, with the help of the Electronic Scanning Microscope (SEM).An EDAX detector was used to check any probable transformation in the consistency of the stents.According to results we conclude that the bending percentage is an important factor for the appearance of particular corrosion / damage types.A correlation between the extension of the overlapping area and the appearance of a certain corrosion type was also observed.A larger overlapping area suggested increase in the damage tension.Particular material is sensitive to certain corrosion types.What is important is that the percentage analysis is presented with a very small change in some points, something that is due to the chlorine reaction contained in the cerum used as blood resemblance with the stents' metal.
Keywords: Implanting stents; Εμφύτευση